EDUCATIONAL PROGRAMS AND EXPERIENCES IN DEVELOPED COUNTRIES OF THE WORLD TO PREVENT RECIDIVISM OF CONVICTED PERSONS - Ikanova Lazokat Sultannazir kizi (Лучшие интеллектуальные исследования, 2024)
Abstract: The importance of prison education is now recognized by many countries. Education is part of a comprehensive range of activities provided to persons serving a sentence of deprivation of liberty, and all of them are aimed at achieving one comprehensive goal - the socialization and reintegration of ex-convicts and the reduction of recidivism.